2017
DOI: 10.1186/s12879-017-2744-7
|View full text |Cite
|
Sign up to set email alerts
|

Shifting trends in bacteriology and antimicrobial resistance among gastrointestinal fistula patients in China: an eight-year review in a tertiary-care hospital

Abstract: BackgroundThe purpose of this study was to determine the shifting trends in bacteriology and antimicrobial resistance of infectious specimens isolated from gastrointestinal (GI) fistula patients over eight years in China.MethodsWe retrospectively reviewed the microbial records of intra-abdominal specimens at a teaching hospital from 2008 to 2015. Study period was divided into the first half (2008–2011) and the second half (2012–2015). All isolates underwent antibiotic susceptibility testing by the micro diluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(47 reference statements)
1
3
1
Order By: Relevance
“…However, data from 2015 showed K. pneumoniae IAI isolate susceptibilities between 80 and 90% to IPM and ETP in our study, which was much higher than the 43.24% susceptibility to IPM reported for K. pneumoniae IAI isolates from a Chinese tertiary-care hospital between 2012 and 2015 [ 15 ], but was in a similar range to Chinese isolates from abdominal trauma-associated IAI collected between 2010 to 2015, with susceptibilities of K. pneumoniae strains to IPM and ETP of 87.5–90.6% [ 16 ].…”
Section: Discussioncontrasting
confidence: 77%
“…However, data from 2015 showed K. pneumoniae IAI isolate susceptibilities between 80 and 90% to IPM and ETP in our study, which was much higher than the 43.24% susceptibility to IPM reported for K. pneumoniae IAI isolates from a Chinese tertiary-care hospital between 2012 and 2015 [ 15 ], but was in a similar range to Chinese isolates from abdominal trauma-associated IAI collected between 2010 to 2015, with susceptibilities of K. pneumoniae strains to IPM and ETP of 87.5–90.6% [ 16 ].…”
Section: Discussioncontrasting
confidence: 77%
“…This study correlates with another study done by Liu et al which showed 100% sensitivity to Vancomycin and Linezolid, while High-level resistant was shown in Penicillin (93.34%), Erythromycin (84.62%), and Ciprofloxacin (73.68%) [16].…”
Section: Singh Et Alsupporting
confidence: 91%
“…Within a relatively short time after the first antibiotics were introduced, bacteria began exhibiting various degrees of resistance ( 1 ). Antibiotic resistance is a global challenge that impacts all pharmaceutically used antibiotics ( 2 , 3 ). In response to the emergent antibiotic resistance, novel strategies are needed to develop new antibiotics, vaccines, and bacitracin ( 4 9 ) and to enhance the effectiveness of existing antibiotics ( 10 13 ).…”
Section: Introductionmentioning
confidence: 99%